Cenni sul sistema sanitario di salute generale e mentale cubano - Carlotto, Alessandra; Ruiz, Alexis Lorenzo (Il sogno della farfalla, 2023)
The aim of this paper is to propose a brief overview on the Cuban healthcare system, highlighting its most important pillars. These include: universalism and equal access to care; collectivism, holistic approach to the patient which integrates both physical and mental health; a crucial role of primary prevention and health education. More specifically, this article focuses on the cure of mental illness, emphasizing the predominance of the psychotherapeutic approach in treating these disorders. Finally, the authors clearly demonstrate how Cuba has admirably managed to establish a successful and competitive healthcare system.